Investigating the energetic disorders and charge-carrier mobilities of active layers via simulating the performances of organic solar cells - Qin, Dashan; Zong, Wei; Zheng, Xiaojian (Semiconductor science and technology, 2025)
The average bandgap, energetic disorder and (effective) charge-carrier mobilities are the three most important optoelectronic parameters of active layer to determine the performance of organic solar cells (OSCs) under 1 sun illumination. Here, the average bandgaps of active layers have been estimated via combing the experimentally measured short-circuit current density and absorptance of device; the energetic disorders and charge-carrier mobilities have been derived from simulations on the performances of OSCs. It is found that the energetic disorder and charge-carrier mobilities of binary active layers depend on the phase mixing of donor and acceptor. Enhancing the phase mixing of donor and acceptor increases the number of the donor and acceptor molecules that form the charge-transfer states, thereby decreasing the energetic disorder. However, it worsens the phase continuity of donor and acceptor at the same time, thereby lowering charge-carrier mobilities. The addition of a third compatible component into binary active layer may decrease the energetic disorder and simultaneously increase the charge-carrier mobility via enhancing the phase mixing of donor and acceptor. The low energetic disorder of active layer is found to underlie the high efficiencies of OSCs; while increasing the charge-carrier mobility of active layer is helpful to improve the efficiencies of devices.